ASME 2008 Noise Control and Acoustics Division Conference 2008
DOI: 10.1115/ncad2008-73024
|View full text |Cite
|
Sign up to set email alerts
|

Noise Source Identification on a Continuous Mining Machine

Abstract: Noise Induced Hearing Loss is the most common occupational disease in the U.S. and of paramount importance in the mining industry. According to data for 2006 from the Mine Safety and Health Administration (MSHA), Continuous Miner operators accounted for 30.2% of underground mining equipment operators with noise doses exceeding the Permissible Exposure Limit (PEL). This figure becomes more significant considering that 49% of the 2006 national underground coal production was extracted using continuous mining met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The distributions from the humps meet at 1 kHz. As mentioned previously, prior studies showed that the frequencies below 1 kHz are attributable to screen body noise, while the frequencies above 1 kHz are due to mechanism housing noise 31,32 . A package of engineering noise controls was developed to address these noise sources, as well as spring chatter noise.…”
Section: Baseline Measurementsmentioning
confidence: 86%
See 2 more Smart Citations
“…The distributions from the humps meet at 1 kHz. As mentioned previously, prior studies showed that the frequencies below 1 kHz are attributable to screen body noise, while the frequencies above 1 kHz are due to mechanism housing noise 31,32 . A package of engineering noise controls was developed to address these noise sources, as well as spring chatter noise.…”
Section: Baseline Measurementsmentioning
confidence: 86%
“…The motor and drive belts were not enclosed due to space constraints in coal preparation plants. Additionally, they were not found to be significant contributors to noise 32 . We created a modular panel-on-frame design with components that weigh less than 222 N (50 lb.)…”
Section: Acoustic Enclosurementioning
confidence: 98%
See 1 more Smart Citation
“…However, this assumed that the operator controlled the continuous mining machine via on board controls, unlike the remote machine controls typically used by industry today. Through the use of remote controls operators are more directly exposed to the noise generated by the conveying system, which has been the focus of recent investigations 12,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Noise generated by the impacts that occur between chain flight bars and conveyor components is particularly severe where the chain traverses its path; at the gear sprocket (front of machine) and tail roller (rear of machine) 14,15 . Early research conducted by BOM concentrated on treatments to reduce CMM conveyor system noise 16 .…”
Section: Introductionmentioning
confidence: 99%